A multihoming-based mobility management scheme to reduce registration delay on proxy MIPv6 domain in NEMO - Islam, Shayla; Hassan Abdalla Hashim, Aisha; Habaebi, Mohamed Hadi; Abdul Latif, Suhaimi; Ismail, Ahmad Fadzil; Hasan, Muhammad Kamrul; Hassan, Wan Haslina (2014)
Registration delay is a significant issue for mobile network due to increase traffic load with handoff latency at the time of frequent movement from one subnet to another of Mobile Router (MR) in NEMO Basic Support protocol (NEMO BSP). Hence, a network-based localized protocol (i.e. PMIPv6) is integrated with NEMO in order to solve these matters. Yet, combining this network-based localized protocol for inter mobility handoff (i.e. movement among different access technology) in NEMO environment is a challenging issue as both MR and its MNNs must be taken into consideration. Therefore, this paper proposes a multihoming-based Early Proxy Binding Update scheme in NEMO (EPBU-NEMO) which is based on FPMIPv6 with predictive mode to reduce registration delay during inter mobility handoff. Moreover, numerical framework is formulated to evaluate the outcomes of the EPBU-NEMO scheme. Lastly, it determines that EPBU-NEMO scheme outperforms the standard NEMO BSP related to signaling cost regardless of increasing the number of MRs as well as cell residence time.